Juegos electrónicos y la violencia filioparental en los estudiantes de la Unidad Educativa San Carlos - Mena Méndez, Yareli Jacqueline (2020)
This research work entitled "Electronic games and filioparental violence in students of the San Carlos Educational Unit", was developed with the objective of supporting the impact of video games on the appearance of aggressiveness towards their parents by adolescents. Likewise, it refers to the degree of influence of the games on the type of interpersonal relationship and how verbal, physical or psychological aggressions against their relatives occur. As for the research methodology, it is exploratory, since it is the one that is carried out with the intention of emphasizing the essential aspects of an investigation. The field and documentary modality will also be used: Field because students, teachers and authorities will be surveyed and; Documentary because we turn to scientific information from bibliographic texts, journals and scientific articles The results obtained give a high significance between electronic games and cases of filioparental violence, demonstrating the agreement between access to electronic games and hostile treatment between children and parents. Of the parents surveyed, 15% said that, at some point, their child has disrespected him or his spouse, 60% said that this has never happened in their home and 25% acknowledged that, on occasion, if this situation has occurred. Finally, the idea that it is important that, within the walls of the home, parents teach and, above all, practice fundamental values in a coexistence, such as mutual respect, despite the fact that their children are much younger in age than them, it will always be necessary to establish respect on both sides.